A report on the practice-in-industry training in fish culture - Garcia, Angel Mangilin (College of Fisheries, University of the Philippines, 1971)
As the title connotes, practice-in-industry training in fish culture deals on the actual application and observation of the methods and practices of fish culture. The aim of said training is to gather know0how and to test the capability of the student undergoing such phase of course. Training in fish culture, like any phase of fisheries industry, is primarily concerned with practical work encountered in the fishpond industry. Furthermore, training encountered is designed to provide a student an intensive practice in the fundamental principles and methods learned in the course. It gives the student a chance to acquire necessary experience and feel the kind of work he faces after leaving college. Three and half months of my training were devoted and undertaken at the U.P. College of Fisheries freshwater experimental pond from December, 1970 up to April, 1971, exclusive of Sundays and Holidays. The work during the training was scheduled daily from eighth o'clock in the morning to four o'clock in the afternoon. However, the remaining two weeks to complete the four months training was conducted in a brackish water fishpond in Batangas, owned by Mr. Juan Gonzales and managed by Mr. Severino Acosta. But the work lasted for more than three weeks to complete the job's scheduled.